CROSS-SECTIONAL STUDY OF IL28B POLYMORPHISMS AMONGST SAUDI ARABIAN AND BRITISH HCV PATIENTS - Qattan, Ilham T; Omer, Waleed. H.; AlOmer, Ibrahim A.; Bereagesh, Samar A.; Kabbani, Kennan M.; Alkhatib, Ahed J; AlGhaithy, Abdul-Aziz A.; Sadeque, Baker B.; Brown, David J.; Emery, Vincent C. (European Scientific Journal, ESJ, 2012)
Several studies published in 2009 suggested that single nucleotide polymorphisms (SNPs) and viral markers in the IL28B gene locus (Ge et al., 2009; Suppiah et al., 2009 and Tanaka et al., 2009) are associated with increased risk of poor response to therapy. IL28B is a member of the interferon (IFN) cytokine family known as IFN III or Lamda (IFN-λ), which includes three types: IFN-λ1 (IL-29), -λ2 (IL-28A) and -λ3 (IL-28B). These are encoded by 3 different genes located on chromosome 19 (Kotenko et al., 2003; Sheppard et al., 2003). rs12979860 genotype (CC, TT, C/T) was the first polymorphism of the IL28B gene to be identified and was associated with a twofold improvement with treatment of HCV infection amongst people of European (P= 1.063 X10ˉ²⁵), Hispanic (P= 4.39 X 10ˉ³) and African-American (P= 2.06 X 10ˉ³) ancestry (Goldstein et al., 2009). Seventy per cent of Caucasians, 40% of African-Americans and 95% of Asians carry at least one copy of the rs12979860C variant allele (Hézode and Chevaliez, 2010). Amongst Egyptians, the CC genotype was significant (p<0.001) for 87.2% in SVR, CT for 25.5% but TT for only 10% and was associated with failure to respond to therapy (Hendy et al., 2011). The response rate was found to be higher amongst the CC and CT patients than the TT patients after 4 weeks of treatment. However, by week 8, viral clearance was more common amongst the CC and CT patients, although the CT rate of clearance was found to be closer to that of the TT than CC patients (Afendy et al., 2011; Chung et al., 2010; Hézode and Chevaliez, 2010; Goldstein et al., 2009). The second polymorphism (rs8099917-genotype (GG, TT, G/T)) was found in individuals of Australian and northern European ancestry. The GG genotype was strongly associated with a null virological response (NVR) to treatment with peg-IFN-α +RBV, whereas patients with the G/T or TT genotypes showed an increased probability of achieving an SVR (Thol et al., 2010; Toyoda et al., 2011). The GT genotype frequency was 42%, and the GG genotype frequency was 16.7% in the responding Egyptian patients (Hendy et al., 2011). Recent data have shown that the SNPs near the IL28B gene are not only associated with an SVR or non-response to treatment with peg-IFN-α + RBV but are also associated with a response to telaprevir-containing regimens (Rallon et al., 2010; Rauch et al., 2010; Akuta et al., 2010). The effects of the IL28B polymorphism on the kinetics of HCV clearance after therapy have also been investigated. Bochud showed that polymorphisms in IL28B were significantly correlated with the first phase of viral decline during peg-IFN-α + RBV therapy of chronic HCV infection, irrespective of HCV genotype (Bochud et al., 2011). Aims - The aims of this study were to investigate the prevalence of IL28B polymorphisms in Saudi Arabian patients infected with hepatitis C virus (HCV), hepatitis B (HBV) and human immunodeficiency virus (HIV) and to compare the prevalence amongst the Saudi Arabian HCV patients with that amongst HCV-infected patients from the United Kingdom (UK). The correlation of the IL28B genotype with responsiveness to therapy was also evaluated. ﻿Methods - This study included 328 patients who received therapy and whose demographic data were collected. The biochemical and virologic parameters were also defined to indicate their response to therapy. An assay to examine the IL28b polymorphism in the human genome was performed, and the rs12979860C/T and rs8099917G/T variants were determined with a real-time PCR platform using an allelic discrimination method and a melting point with dynamic detection of the signals for both variants shown by fluorescent dyes during in vitro amplification. DNA from serum was extracted using the QIA gene (QIAxtractor) and amplified using the rt-PCR Light Cycler 480 supplied by Roche Diagnostic Company. Results - This study illustrated that both of the polymorphisms (RS60 and RS17) interfered with the host response to treatment. The study first identified the HCV patients who achieved SVR and became responders (R). Amongst the patients who achieved SVR, the CC genotype was identified in 19% of them, the CT genotype in 22% and the TT genotype in 38.4 %. A significant correlation between RS-60 and the level of response was observed (p < 0.001). The results of the present study suggest that the non-responding patients (NR) had genotype frequencies for CT of approximately 53%, CC of approximately 50% and TT of 23%. NR and the IL28B (RS-60) genotypes were significantly correlated (p < 0.001), whereas amongst the partially responding patients (PR), similar patterns of frequency for genotypes CC and TT (7.7%) were observed more frequently than for CT (3.2%). RS-60 and partial response was significantly correlated (0.026). Transitional response (TR) patients showed a higher frequency of the TT genotype (23.1%) than the CT genotype (8.1%). However, the CC genotype frequency was the lowest (7.7%). The study also demonstrated that the predominate genotype for the HCV virus in the patients from the Kingdom of Saudi Arabia was 4 (87%). The frequency of RS-17 did not significantly correlate with treatment response (P >0.05). The frequency of RS-17 and RS-60 in the UK samples was not significantly correlated with treatment response (P > 0.05). In addition, in the NR, the HBV frequency of RS-17 GT was 25%, TT 66.3% and GG 0%. In patients who achieved SVR, approximately 47% of the genotypes were GT and 100% were GG; no TT genotypes were identified. The PR group showed a higher frequency for TT (33.3%) than GT (25%); no GG genotypes were identified. The RS-17 (P > 0.05 for all) and RS=60 (P > 0.05) genotype frequencies were not significantly correlated with treatment response. In HIV patients, RS-17 and NR were significantly correlated (P= 0.010). The GG genotype was present in 53%, GT in 57.4% and TT in 22.2% of the patients who did not achieve SVR.﻿In the patients who achieved SVR, TT and GG had a similar frequency (26.3%) and GT had a frequency of 20.4%. In the PR group, TT was the most common genotype (37%), followed by GT (18.5%) and GG (10.5%). No significant correlations were observed between RS-17 and either PR or R (P > 0.05). Treatment response and the frequency of IL28B for the RS-60 genotypes were significantly correlated (P= 0.001). Twenty-one per cent of the patients achieved SVR, with the highest frequency having the CT genotype (26%), followed by CC (11.8%). Forty-seven per cent of the HIV patients failed to respond. The CC genotype was the most common (77%), followed by TT (50%) and CT (40%). The relationship between IL28B for the RS60 genotypes and the NR group was statistically significant (P = 0.023). In the PR group, the most common genotype was TT (40%), followed by CT (23.3%) and CC (5.9%). The relationship between the IL28B RS60 genotypes and PR was statistically significant (P = 0.002). The results for the RS-17 genotype in KSA-HIV correlated significantly with viral load (P = 0.034).﻿﻿